Teaching creative thinking skills and its challenges, strategies and future implications: a narrative of IIUM experience - Badi, Jamal Ahmed Bashier (International Islamic University Malaysia, 2008)
This paper aims at exploring, discussing and analyzing some major issues in teaching creative thinking skills (CTS) based on IIUM experience.1 These issues are challenges encountering trainers and lectures in teaching (CTS), strategies to overcome these challenges, and future implications proposed to enhance the process. It is well recognized worldwide that Edward de Bono is a pioneer in designing tools for teaching creative thinking skills since late sixties last century. Therefore, his tools were adopted and incorporated in the syllabus. Tools include six thinking hats, CoRT lessons, and lateral thinking. As such the discussion will be mainly related to those tools. Descriptive, analytical and critical approaches will be used, based on the author’s experience in classroom teaching and training CTS settings that were conducted at IIUM for the last ten years. To put this experience in an academic setting, the views of those who wrote on the subject will be sought. Hopefully this study will lead to enhance the performance of the lectures who teach the subject at IIUM; it will also help both internal and external auditors to improve teaching the subject, and other experts in Muslim world will be able to give feedback on the experience.